THE COMBINATION OF SECULAR AND RELIGIOUS KNOWLEDGE - U. U. Usanova; V. A. Alimasov (Journals Park Publishing, 2022)
The article discusses the importance of education and especially the importance of the combination of religious and secular knowledge in human life and makes suggestions.
Keywords: Atheism; communism; ideology